2017
DOI: 10.1371/journal.pcbi.1005809
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the strength of quorum sensing crosstalk within microbial communities

Abstract: In multispecies microbial communities, the exchange of signals such as acyl-homoserine lactones (AHL) enables communication within and between species of Gram-negative bacteria. This process, commonly known as quorum sensing, aids in the regulation of genes crucial for the survival of species within heterogeneous populations of microbes. Although signal exchange was studied extensively in well-mixed environments, less is known about the consequences of crosstalk in spatially distributed mixtures of species. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 52 publications
2
30
0
Order By: Relevance
“…With the recent advances in systems and molecular biology, many new studies are being conducted to understand the complex behaviors of microbes that arise due to cellular and spatial heterogeneity [9,[26][27][28][41][42][43][44]. Several studies have shown that many cellular systems exhibit emergent phenomena previously studied in non-biological contexts and that can be explained using physical and statistical mechanical rules [45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…With the recent advances in systems and molecular biology, many new studies are being conducted to understand the complex behaviors of microbes that arise due to cellular and spatial heterogeneity [9,[26][27][28][41][42][43][44]. Several studies have shown that many cellular systems exhibit emergent phenomena previously studied in non-biological contexts and that can be explained using physical and statistical mechanical rules [45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…We developed a model that captured the dynamics of signal exchange and cell growth. The growth of the cells is modeled with a logistic growth equation [9,26],…”
Section: A Reaction-diffusion Modelmentioning
confidence: 99%
See 3 more Smart Citations